(untitled) (Journal of Shaheed Suhrawardy Medical College, 2021)
Background: Ageing is an inevitable process with some specific and distinctive health problems. With increase in life expectancy the elderly population is increasing day by day, so is the concern for the different aspects of their health problems. Objectives: The present study was conducted to find out the proportion of morbidity and morbidity pattern among the elderly population (60 years and above) of a selected rural area of Bangladesh. Methodology: This was a cross-sectional type of descriptive study was conducted from January, 2019 to April, 2019. Two hundred and twenty one elderly people from Kaliakoir Upazilla under the district of Gazipur were interviewed. Data were collected by face to face interview through an interviewer administered semi-structured questionnaire. The study place was selected conveniently and the sampling technique was purposive type of non-probability sampling. Results: Out of 221 respondents 91% (201) had morbidity of any kind related to their health. Common forms of morbidities were musculoskeletal problems (50.3%), hypertension (43.8%), PUD and hyperacidity (27.4%), diabetes mellitus (21.4%) and respiratory problems (19.4%). The mean age of the respondents in this study was 64.97 (± 6.120) years. Maximum proportion (55.2%) belonged to the age group of 60 to 64 years. Among the total 221 respondents 55.7% were female and 44.3% were male. Morbidity among the males was 88.8% and among the females was 92.7%.Most (86.4%) of the respondents were Muslims. Majority (81%) of the respondents was married and only 19% were widow/ers. Fifty five percent of the respondents were literate having different levels of education. The most common occupation among the males was farmer (40%) and among the females was housewife (51.1%).The mean monthly family income was Tk.18,800(±Tk.19210.336) and majority (53.8%) belonged to middle income group (Tk.10001 to Tk.30000). Most (53.8%) of the respondents lived in joint family. Fifty two percent lived in semi pucca house, 78.7% used tube wells as their source of drinking water but unexpectedly 18.6% still used non-sanitary latrines. Out of 201 morbid respondents majority (60.2%) were diagnosed by MBBS doctors and 60.7% were diagnosed in government hospitals. Most (86.6%) of the respondents took some sort of treatment and 10% did not take any treatment. Remaining 3.5% took partial treatment. Most common form of treatment taken by the respondents was medicine (87.4%). Majority (60%) of 20 respondents who did not take any kind of treatment was due to poverty and rest 40% was due to negligence. Conclusion: To build up awareness and to explore the situation in detail, in-depth community based epidemiological study may be carried out. J Shaheed Suhrawardy Med Coll, December 2020, Vol.12(1); 27-32